Investigation of a few oxazolone molecules as corrosion inhibitor for API5LX60 steel in 1N H2SO4 solution - Parijat Burhagohain; Gitalee Sharma; Prankush Malla Bujarbaruah (Egyptian Journal of Petroleum)
Corrosion is recognized as a notable problem in oil sector where API5LX60 steel transmission pipelines are in frequent use. In this report, three oxazolone derivatives as potential corrosion inhibitors were investigated on API5LX60 graded carbon steel in 1N H2SO4 solution in stagnant conditions at concentrations 50–200 ppm. Gravimetric weight loss coupons and electrical resistance corrosion monitoring techniques performed on test samples showed inhibitory properties with best at 200 ppm inhibitor concentration. The results further revealed that the degree of inhibition was concentration dependent. Inhibitor I exhibited the highest inhibition efficiency of 90.70% at 200 ppm concentration. Statistical analysis using multiple linear regression model procreated high R2 value of 0.998 and p-value < 0.0001 asserting a smooth linear dependence of inhibitor efficiency on oxazolone concentration and weight loss of the steel. Again, surface analysis affirmed the formation of protective coating of inhibitor on steel surface. Furthermore, the oxazolone inhibitor adsorbed physically on the steel surface and obeyed the Langmuir isotherm which is evident from the linear correlation coefficient value of 0.9992.